(untitled) (Research, Society and Development, 2020)
The article seeks to characterize in the literature studies of mobile application development in the health area focused on safety in patient care. This is an integrative literature review performed in the MEDLINE, CINAHL, SCOPUS and LILACS databases with original articles published between 2013-2018 in English, Portuguese and Spanish. Data extraction was mediated by the validated Ursi instrument, 2005. The articles were classified according to the level of evidence and the international patient safety goal addressed. 18 articles comprised the review, of which (n = 12, 66%) were published between 2014 and 2017 and 17 (94%) in international journals. There was a predominance of level III studies of evidence (n = 9; 50). As for the public involved in the research, there was a predominance of nurses and nursing academics, as well as hospitalized and domiciled patients. Aiming a better understanding of the ideas, the discussion was arranged in four categories: specifications of the analyzed sample; mobile technology focused on efficient communication; applications for monitoring safe pharmacotherapy and computerization of data collection. It is noted that the characterization of available apps increases the range of options for users to deepen the patient safety theme inserted in digital platforms. Moreover, the detailed levels of evidence in the available publications make this research an input for future research.